While K-ras Is Essential for Mouse Development, Expression of the K-ras 4A Splice Variant Is Dispensable - Plowman, Sarah J. (American Society for Microbiology, 2003)
In mammals, the three classical ras genes encode four highly homologous proteins, N-Ras, H-Ras, and the isoforms K-Ras 4A and 4B. Previous studies have shown that K-ras is essential for mouse development and that while K-ras 4A and 4B are expressed during development, K-ras 4A expression is regulated temporally and spatially and occurs in adult kidney, intestine, stomach, and liver. In the present study, the pattern of K-ras 4A expression was examined in a wide range of wild-type adult mouse tissues, and gene targeting was used to generate K-ras 4A-deficient mice to examine its role in development. It was found that K-ras 4A is also expressed in uterus, lung, pancreas, salivary glands, seminal vesicles, bone marrow cells, and cecum, where it was the major K-Ras isoform expressed. Mating between K-ras(tmΔ4A/+) mice produced viable K-ras(tmΔ4A/tmΔ4A) offspring with the expected Mendelian ratios of inheritance, and these mice expressed the K-ras 4B splice variant only. K-ras(tmΔ4A/tmΔ4A) mice were fertile and showed no histopathological abnormalities on inbred (129/Ola) or crossbred (129/Ola × C57BL/6) genetic backgrounds. The results demonstrate that K-Ras 4A, like H- and N-Ras, is dispensable for normal mouse development, at least in the presence of functional K-Ras 4B.